Current Insights into Exercise-based Cardiac Rehabilitation in Patients with Coronary Heart Disease and Chronic Heart Failure - Nichols, Simon; McGregor, Gordon; Breckon, Jeff; Ingle, Lee (International Journal of Sports Medicine, 2020)
Cardiac rehabilitation is a package of lifestyle secondary prevention strategies designed for patients with coronary heart disease and chronic heart failure. A community-based cardiac rehabilitation programme provides patients with a structured exercise training intervention alongside educational support and psychological counselling. This review provides an update regarding the clinical benefits of community-based cardiac rehabilitation from a psycho-physiological perspective, and also focuses on the latest epidemiological evidence regarding potential survival benefits. Behaviour change is key to long-term adoption of a healthy and active lifestyle following a cardiac event. In order for lifestyle interventions such as structured exercise interventions to be adopted by patients, practitioners need to ensure that behaviour change programmes are mapped against patient’s priorities and values, and adapted to their level of readiness and intention to engage with the target behaviour. We review the evidence regarding behaviour change strategies for cardiac patients and provide practitioners with the latest guidance. The ‘dose’ of exercise training delivered to patients attending exercise-based cardiac rehabilitation is an important consideration because an improvement in peak oxygen uptake requires an adequate physiological stimulus to invoke positive physiological adaptation. We conclude by critically reviewing the latest evidence regarding exercise dose for cardiac patients including the role of traditional and more contemporary training interventions including high intensity interval training.
Keywords: exercise dose; behaviour change; risk factors; clinical outcomes; high intensity interval training